Developing acceptable contraceptive methods: Mixed-method findings on preferred method characteristics from Burkina Faso and Uganda - Brunie, Aurélie (Gates Open Res, 2019)
Background: Unmet need remains high in developing regions. New contraceptive technologies may improve uptake and use. This study examines desirable product characteristics. Methods: We added a module to the female questionnaire of the PMA2020 surveys in Burkina Faso and Uganda and conducted 50 focus group discussions (FGDs) with women, 10 FGDs with men, and 37 in-depth interviews (IDIs) with providers across the two countries. FGDs with women and IDIs with providers included a semi-structured ranking exercise on pre-selected product characteristics. Results: Effectiveness, duration, few side effects, cost, and access were the characteristics most commonly reported as important in choosing a method by survey respondents across both countries. Half or more of women surveyed in each country would like a method that lasts at least one year, while 65% in Burkina Faso and 40% in Uganda said they would use a method causing amenorrhea. Qualitative findings show that women want methods with minimal and predictable side effects. Reactions to increased bleeding were negative, especially in Burkina Faso, but perspectives on reduced bleeding were more mixed. Women and providers preferred methods that are discreet and not user-dependent, and associate duration with convenience of use. Some women in Uganda expressed concerns about the invasive nature of long-acting methods, and cost was an important consideration in both countries. In the ranking exercise, discreet use and few side effects often ranked high, while causing amenorrhea and not requiring a pelvic exam often ranked low. Conclusion: Product development should consider user preferences for success in these settings.